Trunk Muscle Training Augmented With Neuromuscular Electrical Stimulation Appears to Improve Function in Older Adults With Chronic Low Back Pain: A Randomized Preliminary Trial. Issue 10 (October 2016) - Hicks, Gregory E.; Sions, Jaclyn M.; Velasco, Teonette O.; Manal, Tara J.
Abstract : Objectives: To assess the feasibility of a trial to evaluate a trunk muscle training program augmented with neuromuscular electrical stimulation (TMT+NMES) for the rehabilitation of older adults with chronic low back pain (LBP) and to preliminarily investigate whether TMT+NMES could improve physical function and pain compared with a passive control intervention. Materials and Methods: We conducted a single-blind, randomized feasibility trial. Patients aged 60 to 85 years were allocated to TMT+NMES (n=31) or a passive control intervention (n=33), consisting of passive treatments, that is, heat, ultrasound, and massage. Outcomes assessed 3- and 6-month postrandomization included Timed Up and Go Test, gait speed, pain, and LBP-related functional limitation. Results: Feasibility was established by acceptable adherence (≥80%) and attrition (<20%) rates for both interventions. Both groups had similar, clinically important reductions in pain of >2 points on a numeric pain rating scale during the course of the trial. But, only the TMT+NMES group had clinically important improvements in both performance-based and self-reported measures of function. In terms of the participants' global rating of functional improvement at 6 months, the TMT+NMES group improved by 73.9% and the passive control group improved by 56.7% compared with baseline. The between-group difference was 17.2% (95% confidence interval, 5.87-28.60) in favor of TMT+NMES. Discussion: It seems that a larger randomized trial investigating the efficacy of TMT+NMES for the purpose of improving physical function in older adults with chronic LBP is warranted.